Immune response of channel catfish (Ictalurus punctatus) against Ichthyophthirius multifiliis post vaccination using DNA vaccines encoding immobilization antigens. Issue 94 (November 2019) - Xu, De-Hai; Zhang, Dunhua; Shoemaker, Craig; Beck, Benjamin
Abstract: The channel catfish ( Ictalurus punctatus ) immune response against Ichthyophthirius multifiliis (Ich) after vaccination using plasmid DNA vaccines pcDNA3.1-IAg52a and pcDNA3.1-IAg52b, encoding Ich immobilization antigen genes was studied. Parasite infection level, serum anti-Ich antibodies level, fish mortality after theront challenge, and immune-related gene expression were measured. After in vitro transfection of walking catfish gill cells (G1b) with both pcDNA3.1-IAg52a and pcDNA3.1-IAg52b, antigens IAG52A and IAG52B were detected. During the vaccination trial, 76-fold increase in the Iag52b gene expression was observed in the vaccinated fish group h4 post vaccination. Administration of DNA vaccines by IM injection induced significant gene up-regulation in the head kidney, including immunoglobulin M (IgM), cluster of differentiation 4 (CD4), major histocompatibility I (MHC I), and T cell receptor α (TcR-α) from h4 to d5 post immunization. Fish vaccinated with DNA vaccines or theronts showed increased gene expression of the cytokine interferon (IFN-γ), complement component 3 (C3), and toll-like receptor-1 (TLR-1). Anti-Ich antibodies were detected in fish received pcDNA3.1-IAg52a, pcDNA3.1-IAg52b and the combination of both vaccines d10 post vaccination. Fish vaccinated with pcDNA3.1-IAg52b showed mild parasite infection level, partial survival (20%) and longer mean day to death (MDD) after theront challenge. By contrast, a heavy parasite load, 0% survival and short MDD were observed in the sham vaccinated control fish that received pcDNA3.1 (plasmid without genes encoding Ich immobilization antigen). Further research is needed to improve DNA vaccines for Ich that can induce strong protective immunity in fish. Suggested studies include improved transfection efficiency, use of appropriate adjuvants and including additional parasite antigen genes in the plasmid.